The Astronaut's Wife - Rand Ravich; Theron, Charlize; Clea DuVall; Donna Murphy; Joe Morton; Nick Cassavetes; Samantha Eggar; Johnny Depp (USA Mad Chance, 1999)
Astronaut Spencer Armacoust was on a mission when he suddenly lost contact. When he got home, to friends he was the same, but to his wife he was different. She becomes pregnant, but as time progresses she begins to feel like the lives inside of her are not of this world.
Astronaut Spencer Armacoust was on a mission when he suddenly lost contact. When he got home, to friends he was the same...
Rand Ravich
Language : English Subtitles : English
Keywords: Horror; Thriller; SciFi